Factor the high-degree polynomial expression 7x2+42x+63=0

1 answer

To factor the polynomial \(7x^2 + 42x + 63 = 0\), we can start by factoring out the greatest common factor (GCF) from all the terms.

  1. Identify the GCF of the coefficients: The coefficients are \(7\), \(42\), and \(63\), and the GCF is \(7\).

  2. Factor out \(7\):

\[ 7(x^2 + 6x + 9) = 0 \]

  1. Now, we can factor the quadratic \(x^2 + 6x + 9\). We need two numbers that multiply to \(9\) (the constant term) and add up to \(6\) (the linear coefficient).

The two numbers that satisfy this are \(3\) and \(3\):

\[ x^2 + 6x + 9 = (x + 3)(x + 3) = (x + 3)^2 \]

  1. Therefore, we can rewrite the polynomial:

\[ 7(x + 3)^2 = 0 \]

  1. To find the roots, we set \(7(x + 3)^2 = 0\):

\[ (x + 3)^2 = 0 \]

This gives us:

\[ x + 3 = 0 \quad \Rightarrow \quad x = -3 \]

Thus, the completely factored form of the original expression is:

\[ 7(x + 3)^2 = 0 \]

This indicates that the polynomial has a double root at \(x = -3\).